Empowering Paperless Workflows: Networked UDC-Based EDMS for Enhanced Efficiency and Data Security - Salar Jamal Rashid (NTU Journal of Engineering and Technology)
The Internet enables global virtual communication. Ubiquitous Device Connectivity (UDC) aims to facilitate communication between any physical devices, regardless of their location or networking technology. In this paper, smart electronic documentation and authentication are implemented. Transitioning to Electronic Document Management System (EDMS) Implementing UDC will bring advantages to a business by reducing working hours and storage space, thus enhancing the efficiency of the business enterprise plant's operation. A UDC service consists of a camera as an acquisition device; QR codes, encryption, and cloud are used in the system. It will also facilitate paperless documentation for Quality Assurance (QA), Human Resources (HR), and other departments. The implemented system efficiently collected and requested data, allocating it to only authorized persons, and quickly submitted a file for examination and verification. It prevents data duplication and loss, organizes information through historical tracking, and utilizes digital filtering.